A zebrafish Notum homolog specifically blocks the Wnt/β-catenin signaling pathway - Flowers, G. Parker (Company of Biologists, 2012)
Multiple developmental processes require tightly controlled Wnt signaling, and its misregulation leads to congenital abnormalities and diseases. Glypicans are extracellular proteins that modulate the Wnt pathway. In addition to interacting with Wnts, these glycosophosphotidylinositol (GPI)-anchored, heparan-sulfate proteoglycans bind ligands of several other signaling pathways in both vertebrates and invertebrates. In Drosophila, Notum, a secreted α/β-hydrolase, antagonizes the signaling of the prototypical Wnt Wingless (Wg), by releasing glypicans from the cell surface. Studies of mammalian Notum indicate promiscuous target specificity in cell culture, but the role of Notum in vertebrate development has not been studied. Our work shows that zebrafish Notum 1a, an ortholog of mammalian Notum, contributes to a self-regulatory loop that restricts Wnt/β-catenin signaling. Notum 1a does not interact with Glypican 4, an essential component of the Wnt/planar cell polarity (PCP) pathway. Our results suggest a surprising specific role of Notum in the developing vertebrate embryo.